Предмет: Алгебра,
автор: ivanovarimma43
( 5 х - 3 у ) в квадрате - 16х в квадрате
Ответы
Автор ответа:
0
Разложить на множители:
(5х-3у)²-16х²=(5х-3у-4х)(5х-3у+4х)=(х-3у)(9х-3у)=(х-3у)·3(3х-у).
Упростить:
(5х-3у)²-16х²=25х²-30ху+9у²-16х²=9х²-30ху+9у².
(5х-3у)²-16х²=(5х-3у-4х)(5х-3у+4х)=(х-3у)(9х-3у)=(х-3у)·3(3х-у).
Упростить:
(5х-3у)²-16х²=25х²-30ху+9у²-16х²=9х²-30ху+9у².
Похожие вопросы
Предмет: Музыка,
автор: youtubers27
Предмет: Английский язык,
автор: katanagaeva8616
Предмет: Математика,
автор: devackakrasnaa
Предмет: Алгебра,
автор: diana1454